Lithological and glacial geomorphological studies near the erratics terrain, Calgary area, Alberta - Morgan, Alan Vivian (University of Calgary, 1966)
Bibliography: p. 154-163. This study is an attempt to determine the lithology of tills in the minity of the Foothills Erratics Train in order to learn more about the origin of this train, the interrelation between Cordilleran and Laurentide ice sheets, and. the glacial history of the Calgary area. Pebble lithology was determined and. recorded at 1.5.5 sites distributed over the study area, using igneous and metamorphic, carbonate, and brown and purple quartzite pebbles as indicatorso Mega-erratics of similar lithology were noted over the entire map region. Isolithological maps were prepared for the respective indicators whilst distribution maps were drawn for the different mega-erratic groupso In the course of field work on pebble lithology a number of different deposits were mapped These included. widespread lacustrine sediments , spillway systems , shoreline levels, deltas and other indicators of former lake levels, as well as areas of ground and hummocky moraine, glacio-fluvial features , and periglacial structures. Landforms such as drumlins and eskers were also mapped in the field , whilst fluting directions and washboard moraine areas were studied on air photographs. Conclusions were reached as to the origin of many of the above mentioned features which were also utilized in reconstructing the glacial history of the area The Foothills Erratics Train possibly originated as a giant rockslide or rockslides onto the surface of a glacier near Mount Edith Cavell, Jasper The quartzite erratics , many in excess of one hundred tons, were emplaced in the study area during the retreat of the Wisconsin ice , and prior to, or contemporaneous with, glacial Lake Calgary. At least three major glaciers covered the study area the Cordilleran ice sheet, the Erratics Train glacier and the Jaurentide ice sheet . The possibility exists that further glaciers may have been incorporated into the western edge of the Laurentide ice. A periglacial environment existed during the deposition of waterworked gravels which cap Nose Hill ...